EFEKTIFITAS PENGALOKASIAN DANA DESA GUNA PENINGKATAN PEREKONOMIAN MASYARAKAT BERDASARKAN PASAL 72 UNDANG-UNDANG NO.6 TAHUN 2014 TENTANG DESA (STUDI DI DESA MALINAU SEBERANG KEC. MALINAU UTARA KAB.MALINAU KALIMANTAN UTARA) - Novanda Cahya Agustin (Dinamika, 2021)
ABSTRACTThe purpose of this study is to determine the effectiveness of the allocation of village funds related to village development in order to improve the community's economy, to find out the obstacles that occur in the effectiveness of the allocation of village funds in Malinau Seberang Village, Kec. North Malinau Kab. Malinau, North Kalimantan, as well as to find out efforts to resolve the obstacles that occur in the allocation of village funds. The research method uses juridical empirical research, and the research approach used is a sociological juridical approach. The data used are primary and secondary data, then the data analysis technique uses qualitative analysis methods. The results of research on the effectiveness of the allocation of village funds to improve the community's economy based on article 72 of law no. 6 of 2014 in Malinau Seberang Village indicate that it is quite optimal, the implementation of the effectiveness of Malinau Seberang village fund allocation is the result of the work spirit shown by the village government, supervision and anticipation of the misappropriation of village funds by the village government as well as the participation of the community who are cooperating in trying to build the village economy. The inhibiting factors are the difficulty of providing understanding to the community about the aims and objectives of the Clean RT program, the lack of ability of the RT management to coordinate all residents, difficulties in obtaining superior fish seeds and the diversion of funds taken from RT operations and staff. Then the efforts made by the village government are to provide understanding through socialization, ordering fish seeds in another place or city and not reducing the funds used for the RT Bersih program but taking funds from RT operations and staff.Keywords: Effectiveness, Village, Village Economy.ABSTRAKTujuan penelitian ini adalah untuk mengetahui keefektifitasan dari pelaksanaan pengalokasian dana desa terkait pembangunan desa guna peningkatan perekonomian masyarakat, mengetahui hambatan yang terjadi dalam keefektifitasan pengalokasian dana desa di Desa Malinau Seberang Kec. Malinau Utara Kab. Malinau Kalimantan Utara, serta untuk mengetahui upaya penyelesaian dari hambatan yang terjadi dalam pengalokasian dana desa. Metode penelitian menggunakan jenis penelitian yuridis empiris, dan pendekatan penelitian yang digunakan adalah pendekatan yuridis sosiologis. Data yang digunakan adalah data primer dan sekunder, selanjutnya teknik analisa data menggunakan metode analisis kualitatif. Hasil penelitian mengenai efektifitas pengalokasian dana desa guna peningkatan perekonomian masyarakat berdasarkan pasal 72 undang-undang no.6 tahun 2014 di Desa Malinau Seberang menunjukkan bahwa cukup optimal, terlaksananya efektifitas alokasi dana desa Malinau Seberang adalah hasil semangat kerja yang ditunjukkan oleh pemerintah desa, pengawasan dan antisipasi akan adanya penyelewengan dana desa yang dilakukan oleh pemerintah desa serta partisipasi dari masyarakat yang turut bekerjasama dalam berusaha membangun perekonomian desa. Faktor penghambat mengenai sulitnya memberikan pemahaman masyarakat tentang program RT Bersih, kurangnya kemampuan pengurus RT dalam mengkoordinir seluruh warga, kesulitan mendapatkan bibit ikan unggulan dan adanya pengalihan dana yang diambil dari operasional RT dan Staff. Kata kunci: Efektifitas, Desa, Perekonomian Desa.